Phycodes templus isp. nov. from the Lower Devonian of northwestern New Brunswick, eastern Canada - Han, Yaojun; Pickerill, Ron (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1994)
Phycodes templus isp. nov. is described from siliciclastic turbidites of the Wapske Formation of the Tobique Group (Lower Devonian) of northwestern New Brunswick, eastern Canada. The new ichnospecies is characterized by a minimum of two, more typically several, bundled sets of essentially horizontal, broomlike or flabellate, internally structureless, lined burrows. Burrow sets within an individual specimen are interconnected by a single tunnel to form an overall inverted pagoda-shaped structure. The ichnotaxon is believed to have been produced by a vagile deposit feeder, most likely a worm-like organism.